Inclusive education among learners with visual impairments in Masvingo North District, Zimbabwe - Caleb Rangarira Ngwarati; Stella Muchemwa (S&Co Publishing, 2024)
Visually impaired (VI) learners face challenges at school especially in the developed world where resources are scarce. Since 1980, Zimbabwe prioritized universal education, aligning with the ‘growth with equity’ principle and ‘nobody left behind’ concept. The 1987 Education Act emphasized inclusivity. This study draws from three models—Social Model, Critical Disability Theory, and Vygotsky's Socio-Cultural Model—all advocating for educational inclusion. The study investigated inclusive education for visually impaired secondary school students in Masvingo North district, Zimbabwe, aiming to identify improved implementation methods for inclusion. Researchers collected data from 4 schools using questionnaires, interviews and observations. A purposive sample (N=67) of 4 school heads, 20 teachers and 43 students comprising 13 VI and 30 non-visual (non-VI) was used. Results revealed that school heads lacked both the knowledge and enthusiasm to implement inclusive education effectively. Additionally, school infrastructure was often unsuitable for visually impaired students, and teaching resources were limited. Most teachers lacked the necessary skills for both face-to-face and online teaching for visually impaired learners. Moreover, there was a lack of awareness and social support for visually impaired students among non-visually impaired peers, schools, and the community. Based on these findings, researchers concluded that inclusive education for visually impaired students requires further development. Teacher educators should train school heads and trainee teachers to address disabilities in schools, while holding related in-service workshops. The responsible ministry and schools should fund for the necessary resources, and the government should ensure policy execution for inclusive education to flourish in Zimbabwe.